2016
DOI: 10.1016/j.jid.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Searching for the Chokehold of NRAS Mutant Melanoma

Abstract: Up to 18% of melanomas harbor mutations in the neuroblastoma rat-sarcoma homolog (NRAS). Yet, decades of research aimed to interfere with oncogenic RAS signaling have been largely disappointing and have not resulted in meaningful clinical outputs. Recent advances in disease modeling, structural biology, and an improved understanding of RAS cycling as well as RAS signaling networks have renewed hope for developing strategies to selectively block hyperactive RAS function. This review discusses direct and indirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“…We observed that targeting mutant NRAS caused significant tumor regression, demonstrating that continuous NRAS signaling is required fortumor maintenance and progression while implicating the inhibition of mutant NRAS as a therapeutic target. Despite decades of research, specific pharmacological inhibition of NRAS has been unsuccessful to date, and efforts to extinguish oncogenic NRAS signaling continue [8]. Genetic suppression of NRAS Q61R in our model was not sufficient to prevent tumor recurrence as resistant tumors developed after a long latency in the absence of mutant NRAS.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…We observed that targeting mutant NRAS caused significant tumor regression, demonstrating that continuous NRAS signaling is required fortumor maintenance and progression while implicating the inhibition of mutant NRAS as a therapeutic target. Despite decades of research, specific pharmacological inhibition of NRAS has been unsuccessful to date, and efforts to extinguish oncogenic NRAS signaling continue [8]. Genetic suppression of NRAS Q61R in our model was not sufficient to prevent tumor recurrence as resistant tumors developed after a long latency in the absence of mutant NRAS.…”
Section: Discussionmentioning
confidence: 93%
“…Attention has now turned to other genetic subgroups of melanoma, with clinical trials showing the potential utility of targeting the MEK/ERK signaling pathway in NRAS mutant melanoma [8,9,29]. Despite initially encouraging results, the duration of response to MEK inhibitors in this setting is limited, with treatment failure being rapid and resistance being near universal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other attempts to target mutant NRAS are summarized elsewhere in detail, but, to date, have not shown clear success in vivo [17]. Hence, indirect targeting of NRAS signaling via inhibition of molecules further downstream in the MAPK pathway, such as MEK or ERK has evolved as an alternative strategy to combat NRAS-mutant melanoma.…”
Section: Drug Evaluation Koelblinger Dornbierer and Dummermentioning
confidence: 99%